Colloidal Superstructures with Triangular Cores: Size Effects on SERS Efficiency - Hoeller, Roland P. M.; Kuttner, Christian; Mayer, Martin; Wang, Ruosong; Dulle, Martin; Contreras-Caceres, Rafael; Fery, Andreas; Liz-Marzan, Luis M. (ACS Photonics, 2020)
The design of colloidal nanostructures as surface-enhanced Raman scattering (SERS) substrates requires control over both structural and optical characteristics. A widespread expectation is that the SERS efficiency depends crucially on whether the plasmonic excitation matches the exciting laser wavelength. However, also the balance between radiative (scattering) and nonradiative (absorbing) properties plays a major role, regarding both the efficiency of near-field enhancement and the experimentally observed signal intensity. We present a study of the influence of mode-excitation matching and extinction characteristics for core/satellite superstructures, comprising gold nanotriangles decorated with small gold nanospheres. The variation of the core size and aspect ratio allowed tuning the main coupled mode between 700 and 800 nm, from off-resonant through resonant at 785 nm, as well as tuning extinction contributions, from dominantly absorbing to dominantly scattering. We observed additional gains of 1-2 orders of magnitude in signal enhancement, which were correlated to core size and diffuse optical properties. Our findings indicate a competition between SERS enhancement and increased scattering losses in larger assemblies. Thus, a balance of optical parameters is required for efficient SERS and the development of assemblies as advanced sensing devices.
CRIS-Team Scopus Importer:2022-04-14
Keywords: diffuse-reflectance spectroscopy; electric field enhancement; enhanced spectroscopy; ensemble plasmonics; self-assembly; small-angle X-ray scattering